Influence of thickness variation on the buckling load in plates made of functionally graded materials - Mozafari, Hamid (EuroJournals, Inc., 2010)

(untitled)
n this paper, a simply supported plate made of Functionally Graded Materials (FGM) with linearly varying thickness is considered. The material properties are assumed to vary as a power law though the plate thickness. Based on higher-order theory assumptions, the equilibrium, stability equations and the relations for pre-buckling loads of the plate under mechanical load are obtained using a variational formulation. The equations are based on Love-Kirchhoff hypothesis and the Sanders non-liner strain-displacement relations. The closed form solution for the buckling load is obtained and the result is verified against known case i.e. a plate with constant thickness. The buckling load is derived by employing the weighted residual approach. Finally, different plots indicating the variation of buckling load vs. different FGM materials, geometries and loading conditions were obtained.